2018
DOI: 10.1038/s41397-018-0065-x
|View full text |Cite
|
Sign up to set email alerts
|

Replication of the pharmacogenetic effect of rs678849 on buprenorphine efficacy in African–Americans with opioid use disorder

Abstract: Many patients with opioid use disorder do not have successful outcomes during treatment but the underlying reasons are not well understood. An OPRD1 variant (rs678849) was previously associated with methadone and buprenorphine efficacy in African-Americans with opioid use disorder. The objective of this study was to determine if the effect of rs678849 on opioid use disorder treatment outcome could be replicated in an independent population. Participants were recruited from African-Americ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 48 publications
1
14
1
1
Order By: Relevance
“…The missing data analyses showed genotype by medication effects with the same direction and magnitude as those in the primary analyses. Thus, although we did not replicate the findings of Crist et al (2013 , 2019 ) of a moderating effect of rs678849 on the response to buprenorphine in AAs, we found such an effect in EAs, which Crist et al (2013) did not.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…The missing data analyses showed genotype by medication effects with the same direction and magnitude as those in the primary analyses. Thus, although we did not replicate the findings of Crist et al (2013 , 2019 ) of a moderating effect of rs678849 on the response to buprenorphine in AAs, we found such an effect in EAs, which Crist et al (2013) did not.…”
Section: Discussioncontrasting
confidence: 99%
“…The study showed no moderating effect of the SNP in the 566 European-American (EA) participants ( Crist et al, 2013 ). In an independent sample of 55 AA buprenorphine-treated patients ( Crist et al, 2019 ), the risk ratio for opioid-positive UDS associated with the CC genotype was 1.69, thereby replicating the initial finding that Crist et al (2013) obtained in AAs, but not EAs. Combining data across the 2 studies, buprenorphine-treated AA patients with the CC genotype had opioid-positive UDS 56.3% of the time, compared with 30.7% for patients in the combined CT and TT genotype groups ( P < .0001).…”
Section: Introductionsupporting
confidence: 64%
See 1 more Smart Citation
“…In addition, several studies have investigated the effects of OPRD1 polymorphisms on treatment outcomes in OUD. For example, the major allele of rs678849 has been associated with higher relapse rates among African American OUD patients undergoing buprenorphine treatment, as indicated by positive opioid urine tests (148, 149). Interestingly, the major allele was initially associated with lower relapse rates among African American OUD patients on methadone treatment (148), but this association was not replicated (149).…”
Section: The Opioid Receptor Systemmentioning
confidence: 99%
“…For example, the major allele of rs678849 has been associated with higher relapse rates among African American OUD patients undergoing buprenorphine treatment, as indicated by positive opioid urine tests (148, 149). Interestingly, the major allele was initially associated with lower relapse rates among African American OUD patients on methadone treatment (148), but this association was not replicated (149). Jones et al (147) reported an association between rs678849 and abstinence-induced opioid withdrawal severity; however, it did not withstand a multivariate analysis.…”
Section: The Opioid Receptor Systemmentioning
confidence: 99%